Beothuk materials, Frank Siebert Papers - Siebert, Frank T. (Frank Thomas), 1912-1998 (1818)
The Beothuk materials in the Siebert Papers are limited to two manuscripts, one in Series IV and the other in Series V. Additional materials may be included under the heading of "Proto-Algonquin."